Access to healthcare in Chilean prisons: an inmates' perspective - GE Sanhueza; J Candia (Sociedad Española de Sanidad Penitenciaria, 2019)
Abstract Objectives: To analyze the perception of access to Chilean prisons in a representative national sample of persons deprived of liberty as well as to examine the most important covariates of such access. Materials and methods: This study uses secondary data from the First National Survey on the Quality of Prison Life (2014), which investigated inmates' perceptions regarding access to health services inside the prisons. To do this, it uses descriptive statistics and a logistic regression model. Results: Descriptive results at the national level show that access to health services in prisons tends to be "difficult" (44.7% of cases in this category). Multivariate logistic regression results indicate that men (OR=0.43) and those who reported better infrastructure (OR=0.70) were less likely to report "difficult access to health services". On the other hand, prison inmates (OR=1.61) and those who had reported higher levels of mistreatment (OR=1.26) were associated with a higher probability of reporting "difficult access to health services". Discussion: Our study suggests that access to health care is dynamically linked to other aspects of life within prisons such as the composition of the prison population (gender), some of the material aspects of prisons (infrastructure, type of facility), and even some relational aspects (level of mistreatment/abuse). Future studies could further extend the debate on healthcare in prisons, incorporating more complex both variables and analyses.